Effects of Heparin, Typhoid Vaccine and Thrombophlebitis on Factor X Metabolism in the Dog - Takeda, Y; Arai, H (Thrombosis and Haemostasis, 1978)
Studies were made of the effects of heparin, typhoid vaccine and thrombophlebitis on factor X (F.X) metabolism in dogs, using 125-labelled F.X (125I-F.X) as a tracer. 10 healthy male dogs were used for control study and 5 male dogs were used for each of other studies. Plasma F.X concentration was measured by a solid-phase radioimmunoassay. In the control dogs, the plasma F.X concentration was 2.4 ± 0.2 (SD) mg per dl, the plasma F.X (x) was 1.2 ± 0.1(SD) mg per kg, the halflife of plasma 125I-F.X(t½) was 0.5 ± 0.01 (SD) days, the fractional catabolic rate (j3p) was 2.4 ± 0.1 (SD) per day and the catabolic flur (J3pX) (synthesis rate) was 2.9 ± 0.7 (SD) mg per kg per day. These results were not appreciably altered in heparinized dogs. However, a single intravenous injection of 2 ml typhoid vaccine caused a shortened t½ of 0.38 ± 0.01 (SD) days and a decrease of plasma F.X concentration to 1.3 ± 0.13 (SD) mg per dl. Studies in heparinized dogs showed similar effects of typhoid vaccine. Next, thrombophlebitis was produced by a previous method and its effects on F.X metabolism were studied. No detectable alterations of F.X metabolism were found. These results indicate that in health most F. X is directly catabolized without the formation of activated F.X (F.Xa), that the observed effects of typhoid vaccine are mostly due to an acceleration of the direct catabolism of F.X without F.Xa formation and finally that localized thrombophlebitis has no appreciable effects on F.X metabolism.